Drake Harlequin escorting its family - Harrison, Jeffery (Wildfowl, 1967)
On 5th August, 1966, at Grund, Skorradalur, West Iceland, a drake Harlequin Histrionicus histrionicus was found still in full plumage, closely escorting its duck and four ducklings, which were then about a month old... Two facts make this event most unusual. First, that the drake should have remained in company with the female and young, and second, that it should have failed to moult into eclipse plumage. The second fact is highly likely to be dependent upon the first.